Indonesia’s Nurcholish Madjid and Abdurrahman Wahid as Intellectual ‘Ulamā’: The Meeting of Islamic Traditionalism and Modernism in neo-Modernist Thought - Barton, Greg (Studia Islamika, 1997)
Indonesian Islamic discourse of the modern record Nurcholish Madjid and Abdurrahman Wahid as the two main characters for the development of a reform movement known as neo-modernism movement. The question that should be asked is: why neo-Modernist Islamic thought this was so a place among Indonesian Muslims?DOI: 10.15408/sdi.v4i1.786